Analysis of individual procedural features of consideration of individual labor disputes in the courts of the Republic of Kazakhstan - Seidimbek, A.A. (Bulletin of the Karaganda University “Law Series”, 2022)
The article defines the essence of the interpretation of the definition of individual labor disputes in the scientific literature and legislative acts. Separate procedural features of consideration of individual labor disputes in the courts of the Republic of Kazakhstan are studied in detail. Such features as the terms of applying to the court for the resolution of a labor dispute (statute of limitations), the jurisdiction of labor disputes, the procedural status of the parties and participants in labor cases, evidence in the labor court, the court’s decision on an individual labor dispute and its execution are disclosed. It is concluded that the analysis of the procedural features of the consideration of labor cases in the courts indicates the insufficient effectiveness of the system of protection of labor rights of citizens by the norms of the current labor and civil procedural legislation. The conducted research has shown the need to develop and adopt new procedural rules that ensure the resolution of labor disputes. To eliminate the shortcomings identified during the study, recommendations on improving the procedural and legal mechanism for resolving labor disputes in the Republic of Kazakhstan based on the standards of the International Labor Organization, the best practices of foreign countries and the doctrine are substantiated. The creation of an effective mechanism for resolving labor disputes will ensure a balance of interests of employees and employers and strengthen the effectiveness of procedural mechanisms in the field under study.